0352 Compliance to Sleep Recommendations: A Big Data Analysis In Users of a Consumer Sleep Technology. (25th May 2022) - Raymann, Roy; Watson, Nathaniel; Gahan, Luke; Gottlieb, Elie
Abstract: Introduction: The National Sleep Foundation has published sleep time duration (Hirshkowitz et al., 2015) and sleep quality (Ohayon et al., 2017) recommendations across the lifespan based on expert panel input. These recommendations offer sleep guidance to millions of individuals. Many individuals are using commercially available sleep tracking devices to measure their sleep. We analyzed the data of two non-contact radiofrequency sleep measurement devices (SleepScore Max (SleepScore Labs) and S+ (ResMed), both validated against PSG) to determine how well the users of these devices are sleeping. Methods: Total Sleep Time (TST), sleep latency (SL) and sleep efficiency (SE) data of 40, 892 users between 15 and 98 years old were used in this analysis, covering 5, 513, 369 nights of data, and averages per user were calculated. In alignment with the aforementioned papers, the data were split in 3 age groups; Young Adults (18-25), Adults (26-64) and Older Adults (>=65), and the criteria as listed were used, classifying the sleep indicators in 3 bins; Appropriate/Recommended, Uncertain/ May be Recommended, and Inappropriate/Not Recommended. Proportion of users meeting the Appropriate/Recommended, Uncertain/May be Appropriate and Inappropriate/Unlikely were calculated for each age group. Results: In the Young Adults group most users had an Appropriate SL (SL<= 30 min; 79.7 %), an Appropriate SE (SE>=85%; 53.6 %), but only 30.0% had a Recommended TST (7 to 9 h.). In the Adult group, larger proportions of users met on average the Appropriate measures for SL (SL<= 30 min; 84.8%), SE (SE>= 85%; 58.4%), but only 27.3% slept on average the Recommended hours (TST 7 to 9 h). In the Older Adults group, the average SL and SE was considered Appropriate for most elderly users (SL<30min; 84.3: SE>=85%; 59.6%), but only 28.2% slept the Recommended amount (TST 7 to 8 h). Conclusion: 30% or less users slept on average the recommended amount, whereas slightly over half of the users showed the recommended sleep efficiency, and at least 79.7% fell on average asleep within 30 minutes. These results show that sleep improvement campaigns need to focus on extending the sleep duration and sleep hygiene to improve SE. Support (If Any):